An innovative semiconducting Ni(II)-metallogel based robust random access memory (RRAM) device for advanced flexible electronics applications - Arpita Roy; Subhendu Dhibar; Saurav Kumar; Sangita Some; Parul Garg; Pradip Ruidas; Subham Bhattacharjee; Ashok Bera; Bidyut Saha; Soumya Jyoti Ray (Scientific Reports)
Abstract A highly effective method for creating a supramolecular metallogel of Ni(II) ions (NiA-TA) has been developed in our work. This approach uses benzene-1,3,5-tricarboxylic acid as a low molecular weight gelator (LMWG) in DMF solvent. Rheological studies assessed the mechanical properties of the Ni(II)-metallogel, revealing its angular frequency response and thixotropic behaviour. Field emission scanning electron microscopy (FESEM) showed a complex rocky network structure, while transmission electron microscopy (TEM) identified rod-shaped formations. Energy dispersive X-ray (EDX) mapping confirmed the chemical composition, and Fourier transform infrared spectroscopy (FTIR) alongside X-ray photoelectron spectroscopy (XPS) provided insights into the metallogel’s formation mechanism. Schottky diode structures which were fabricated with this Ni(II)-metallogel exhibited notable charge transport properties. Moreover, resistive random access memory (RRAM) devices using NiA-TA demonstrated bipolar resistive switching with an ON/OFF ratio of ~ 110 and durability over 5000 cycles. In this work, logic gate circuits were designed using a 2 × 2 crossbar array. This work highlights the potential of Ni(II)-metallogels for non-volatile memory, neuromorphic computing, flexible electronics, and optoelectronics. Their easy fabrication, reliable switching, and stability make them promising candidates for advanced technologies, offering new opportunities for in-memory computing.